Kegiatan Tari Kreatif sebagai Stimulasi Emosi Positif Anak Usia Dini: Studi Kualitatif di TK IT Bunayya - Amanda Hijriani; Dea Miftahul Jannah; Fadillah Ajeng Ningrum; Nur Fadillah; Hilda Zahra Lubis (CV Edujavare Publishing, 2026)
The purpose of this study was to examine how creative dance activities can stimulate positive emotions in early childhood at TK IT Bunayya Medan. The approach used was descriptive qualitative with observation, interview, and documentation methods for teachers and children in group B. The results showed that creative dance activities can stimulate expressions of happiness, increase self-confidence, and strengthen children's social relationships. Creative dance also provides space for children to express their feelings spontaneously and freely. With a fun approach, dance becomes an effective medium in forming positive emotions in early childhood.